The Ambiguity of Men's Hegemony In American - Supriyono (ARRUS Journal of Social Sciences and Humanities, 2021)
Women in male domination and at the same time defends men with the dominance they have. This shows that there is an ambiguous attitude of a woman in responding to the discourse of male domination, injustice in the role of women and affirming women's resistance to male domination. From this, the main problem is the subject's response in dealing with the discourse of male domination through women's resistance strategies through participation in society. The concept or theory and research method used is hegemony. The results obtained are the idea of equality in education being used as a resistance strategy in the discourse of male domination and at the same time strengthening women's resistance to male domination. In addition, the strategy also developed the idea of women's strength based on educational equality, namely through access to higher education